Discursive and visual management technologies in urban sociology - Sergey L. Melnikov, Valentina I. Gostenina, Rafael K. Karneev, Galina V. Makarova, (Opción, 2019)
The research objective is to measure the urban space in terms of social culture and describe the visual and discursive space, revealing the possibilities for self-organization processes of citizens’ identification via signification method of the discourse semantic system, grouping and typology of empirical data, based on social practices of citizens and their perception of space as attractive and prestigious. As a result, accommodation is developed on a special project in contrast to the typical, serial construction of blocks. In conclusion, the spatial action system is converted to a discrete connection and the action space is transformed into the image space